SURVEI MINAT MASYARAKAT TERHADAP PERMAINAN TONNIS DI KABUPATEN DEMAK (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2014)
Tonnis  game  is  pract icall y  a  new  sport   in  t he  community  Demak,  the  game  has  a  val ue  t onnis  practical, economical or cheap and give pleasure, so i t  can be received wel l by the public.  Issues raised in t his  st udy is howthe  public  interest   in  t he  game  t onni s  in  Demak.  The  purpose  of  this  study  i s  to  det ermine  how  much  publ icinterest in the game  t onnis in Demak. Vari abl e in thi s study is the publ ic interest   in t he game tonnis in Demak.To  test  the  validty  of  using  t he  product   moment   formula  and  alpha  rel iability  test  using  the  f ormul a.  Dat a analysi s  in  this  research  is  descript ive  data  analysis.  The  result s  showed  that   the  publ ic  int erest   in  the  gametonnis  in  Demak  incl uded  in  t he  category  is  as  high  as  132  respondents  (48.88%) ,  93  respondents  (34.44%)incl uded  in  the  high  crit eria,  34  respondent s  (12.59%)  were  incl uded  in  the  criteria,  and  11  respondents(4,074%)  included in  the low  category. Concl usions  based  on t he  results of t he study  is that the  average publ \ic interest  in playing  on  tonnis  in  Demak  included  in  the  very  high cat egory.  Advi ce  from  the  author  of,  among others,  for  Unnes  institutions  shoul d  be  heavily  socialized  tonnis  game,  especially  in  the  village  knew  nothing about  the  game  tonnis  that  publ ic  int erest  in  the  game  tonnis Demak  increase  even  more  so  tonnis  can  grow more  rapidly  again.